Performance evaluation for Universal Grammar Engine - Cao, Silu (Auckland University of Technology, 2011)
The technology of natural language processing (NLP) in the field of Artificial Intelligent (AI) research has made much progress, enabling computers to parse human languages both in spoken and written form. Program that recovers the underlying syntactic structure of a sentence is known as a parser. This project focuses on the evaluation of one such parser developed by Professor Yeap. The parser is codenamed the Universal Grammar Engine (UGE) and it is developed to explain how children understand language. UGE is a newly developed parser. Its rules and performance are in need of evaluation.
Keywords: Natural Language Processing; NLP parser evaluation